The whale's tale and the otter's side of the story : a book to read from front to back and back to front - Messner, Kate (Clarion Books, an imprint of HarperCollins Publishers, 2026)
"A boastful whale and a showboating otter compete in a battle of words to prove that each is the greatest animal ever to swim the seas. Read one way, the first-person text brags about whales' superiority; read the other way, it extols how much better otters are. Using true information about the two marine species to make both arguments... [this reversible book illustrates] how the same words can be used to express contradictory opinions when speakers have a one-sided view of the world"--